Exploring the Feasibility of Implementing Entrustable Professional Activities in Workplace-based Training: Insights from Pharmacy Educators - Tarik Al-Diery (17785685) (2025)
Objective To explore the feasibility of adapting and implementing pharmacy entrustable professional activities (EPAs) in workplace-based training. Methods Pharmacy faculty, experienced workplace-based pharmacy educators and practicing pharmacists representing various practice settings were recruited for focus group interviews to explore their perspectives on the feasibility of incorporating 15 EPAs reflecting entry-level pharmacy practice. Interview questions were derived from the validated Quality of Entrustable Professional Activities (QUEPA) rubric. Participants were also asked to provide their views on the facilitators and barriers to introducing EPAs in workplace-based training. Results Five focus groups were conducted with a total of 24 participants between October and November 2023. Four key themes emerged regarding the feasibility of adapting and implementing the 15 EPAs: (1) clarity and measurability of entry-level tasks, (2) limitations and restrictions in EPA implementation, (3) environmental facilitators, and (4) supervisor influence on entrustment decision-making. Participants reported that successful EPA adaptation requires addressing regulatory and contextual barriers, training supervisors in EPA usage, and ensuring EPAs remain adaptable to evolving professional and health care needs. Conclusion The validated QUEPA rubric provided a systematic approach to exploring the incorporation of EPA statements in workplace-based training. Participants recognized the potential of EPAs to support curriculum development and expand pharmacists’ scope of practice. Supervisor-dependent influence on entrustment decision-making emerged as a notable factor that could impact the feasibility of EPA adaptation and implementation. Continuous refinement and active stakeholder collaboration are essential for the effective use of EPAs as a supportive educational framework. Other Information Published in: American Journal of Pharmaceutical Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajpe.2025.101474